Substance Use in Pregnancy: Identifying Stigma and Improving Care - Weber, Andrea (2021)
This review examines the impact of stigma on pregnant people who use substances. Stigma towards people who use drugs is pervasive and negatively impacts the care of substance-using people by characterizing addiction as a weakness and fostering beliefs that undermine the personal resources needed to access treatment and recover from addiction, including self-efficacy, help seeking and belief that they deserve care. Stigma acts on multiple levels by blaming people for having a problem and then making it difficult for them to get help, but in spite of this, most pregnant people who use substances reduce or stop using when they learn they are pregnant. Language, beliefs about gender roles, and attitudes regarding fitness for parenting are social factors that can express and perpetuate stigma while facilitating punitive rather than therapeutic approaches. Because of stigmatizing attitudes that a person who uses substances is unfit to parent, pregnant people who use substances are at heightened risk of being screened for substance use, referred to child welfare services, and having their parental rights taken away; these outcomes are even more likely for people of color. Various treatment options can successfully support recovery in substance-using pregnant populations, but treatment is underutilized in all populations including pregnant people, and more knowledge is needed on how to sustain engagement in treatment and recovery activities. To combat stigma when working with substance-using pregnant people throughout the peripartum period, caregivers should utilize a trauma-informed approach that incorporates harm reduction and motivational interviewing with a focus on building trust, enhancing self-efficacy, and strengthening the personal skills and resources needed to optimize health of the parent-baby dyad.